Peran Kewirausahaan dalam Mengatasi Pengangguran - Mella Junita (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
Entrepreneurship plays a very important role in addressing unemployment through the creation of new jobs, increased innovation, and contributions to economic growth. This research aims to analyze the role of entrepreneurship in reducing unemployment by identifying factors that influence entrepreneurial success and examining government support and entrepreneurship education. The literature review results show that entrepreneurship can provide effective solutions in reducing unemployment rates, especially in rural and underdeveloped areas. Support in the form of access to capital, entrepreneurship education programs, and conducive regulations is crucial in supporting entrepreneurial development. In addition, social entrepreneurship also has great potential in addressing unemployment issues by creating social value besides economic profit. This research provides policy recommendations that can support the development of entrepreneurship as a strategic solution to reduce unemployment and improve community welfare.